Contactless heart rate measurement in newborn infants using a multimodal 3D camera system - Svoboda, Libor; Sperrhake, Jan; Nisser, Maria; Zhang, Chen; Notni, Gunter; Proquitté, Hans (Frontiers in Pediatrics, 2022)
Newborns and preterm infants require accurate and continuous monitoring of their vital parameters. Contact-based methods of monitoring have several disadvantages, thus, contactless systems have increasingly attracted the neonatal communities´ attention. Camera-based photoplethysmography is an emerging method of contactless heart rate monitoring. We conducted a pilot study in 42 healthy newborn and near-term preterm infants for assessing the feasibility and accuracy of a multimodal 3D camera system on heart rates (HR) in beats per minute (bpm) compared to conventional pulse oximetry. Simultaneously, we compared the accuracy of 2D and 3D vision on HR measurements. The mean difference in HR between pulse oximetry and 2D-technique added up to + 3.0 bpm (CI -3.7 – 9.7; p = 0.359, limits of agreement (LOA) ± 36.6). In contrast, 3D-technique represented a mean difference in HR of + 8.6 bpm (CI 2. – 14.9; p = 0.010, LOA ± 44.7) compared to pulse oximetry HR. Both, intra- and interindividual variance of patient characteristics could be eliminated as a source for the results and the measuring accuracy achieved. Additionally, we proved the feasibility of this emerging method. Camera-based photoplethysmography seems to be a promising approach for HR measurement of newborns with adequate precision; however, further research is warranted.